Mengoptimalkan Penghematan Pajak Penghasilan Pada Perusahaan Daerah Canda Bhirawa - Yorie, Shella Nighta (Disclosure: Journal of Accounting and Finance, 2023)
This research aims to determine the analysis of Article 23 Income Tax on rental services in optimizing tax savings. The analysis method is by calculating Article 23 Income Tax using the Gross-Up Method and comparing the amount of corporate income tax before and after the gross-up method. This is a descriptive research with a quantitative approach to analyze, explain, and conclude the analysis of Article 23 Income Tax on rental services as an effort to optimize tax savings in the Canda Bhirawa Regional Company, Kediri Regency. The data collection techniques in this study were documentation and interviews about the financial data of the Canda Bhirawa Regional Company. The results of this study show that gross-up calculations of Article 23 Income Tax were applied to fertilizer transportation services, resulting in an increase in the rental expenses for fertilizer transportation vehicles of Rp49,484,694. This increase will affect the amount of taxable profit for the company and successfully save the company's income tax by using the gross-up method for rental services of fertilizer transportation vehicles, with savings of Rp. 10,886,632.65. This difference was obtained from the calculation of corporate income tax which initially amounted to Rp235,565,197 but became Rp224,678,564 after applying the gross-up method. Based on the above explanation, it is known that the use of Article 23 Income Tax Gross-Up Method can optimize the tax burden of companies.